Aspek Sosial dalam Novel Padang Bulan Karya Andrea Hirata: Tinjauan Sosiologi Sastra dan Implementasinya dalam Pembelajaran Sastra di SMK Muhammadiyah 1 Pemalang - Hakim, Lungit Nurman, Drs. Adiyana Sunanda, M.Pd (2017)
This study aims to: (1) describe the structure that builds Padang Bulan novel by Andrea Hirata (2) describe how the social aspects contained in the Padang Bulan novel by Andrea Hirata (3) describe the implementation of the results of the analysis of the social aspects of the Padang Bulan novel by Andrea Hirata as a literary learning materials in SMK Muhammadiyah 1 Pemalang. This research is a qualitative descriptive research. The data in this study is in the form of words, phrases, clauses, sentences contained in Padang Bulan novel by Andrea Hirata. Sources of data in this research is the Padang Bulan novel by Andrea Hirata. Data collection techniques in this study is the engineering literature, see, and record. Data analysis techniques in this study is the dialectic of data analysis techniques. The validity of the data in this study using triangulation sources. The results of this study indicate that: (1) the structure of the novel Padang Bulan builders can be described as follows. The themes in the novel by Andrea Hirata Padang Bulan is a struggle daughter achieve his goal. Grooves contained in Padang Bulan novel is the groove forward. Figures contained in the novel Padang Bulan is Enong, Ikal, Zinar, Detective M. Nur, Jose Rizal, Syalimah, Zamzami, Nizam's mother, Ikal father, Ikal Mother, Ikal Uncle, Ikal aunt, Mrs. Indri, Sirun, A Ling, Syahdan , Trapani, Ninochka, Margareth, Alvin. Background in Padang Bulan novel is divided into three: a background that is in Belitong Island, Tanjong Pandan, Coming Poor Village, Tanjung Pinang. Timescapes occur more or less in 1990. The social background of the novel describes the Malay community's social life. (2) the social aspect in Padang Bulan novel consists of four aspects: social processes, social change, social problems, social structure. (3) the results of the analysis of the social aspects of the novel Padang Bulan is implemented as a learning material literature in SMK Muhammadiyah 1 Pemalang class XII using core competence and basic competencies 3.1 and 4.1.